2009
DOI: 10.1002/jmri.21999
|View full text |Cite
|
Sign up to set email alerts
|

Short echo time 1H MRSI of the human brain at 3T with adiabatic slice‐selective refocusing pulses; reproducibility and variance in a dual center setting

Abstract: Purpose: To assess the reproducibility of 1 H-MR spectroscopic imaging (MRSI) of the human brain at 3T with volume selection by a double spin echo sequence for localization with adiabatic refocusing pulses (semi-LASER). Materials and Methods:Twenty volunteers in two different institutions were measured twice with the same pulse sequence at an echo time of 30 msec. Magnetic resonance (MR) spectra were analyzed with LCModel with a simulated basis set including an experimentally acquired macromolecular signal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 38 publications
(60 reference statements)
11
42
0
Order By: Relevance
“…The average concentrations of quantified metabolites reported in this study matched reasonably well with recently reported values that were obtained from the same brain regions (4,6,8,24-27). In all 108 analyzed spectra, 10 (in WM) – 11 (in GM) metabolites were quantified with an average CRLB of less than 20%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The average concentrations of quantified metabolites reported in this study matched reasonably well with recently reported values that were obtained from the same brain regions (4,6,8,24-27). In all 108 analyzed spectra, 10 (in WM) – 11 (in GM) metabolites were quantified with an average CRLB of less than 20%.…”
Section: Discussionsupporting
confidence: 90%
“…The increased accuracy in detection of neurochemical profiles at UHF is supported by the lower CoV compared to other studies (8,10,25,26,28-33). This suggests that metabolites involved in inhibitory and excitatory neurotransmission, such as NAAG, Glu and Gln, can now be detected with higher accuracy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our findings for the concentrations of choline, creatine and Glx in NAWM compared with GM are consistent with previous studies in healthy controls [12, 16, 17]. …”
Section: Discussionsupporting
confidence: 93%
“…The spectrum of disorders for which (172,173). Importantly, standard clinical hardware generates reproducible MR spectroscopy data from the human brain in a multicenter setting provided spectroscopy at 3.0 T (174), and coefficients of variance less than 10% were reported for tNAA, tCr, tCho, and mIns with MR spectroscopic imaging at 3.0 T Acknowledgments: The initiative for the MRS Consensus paper was proposed by Risto Kauppinen, MD, PhD, in the MR spectroscopy session of the 8th Biennial Minnesota Workshop on High and Ultra-high Field Imaging held in Minneapolis, Minn, in October 2011.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%